2013
DOI: 10.1016/j.chemosphere.2012.08.049
|View full text |Cite
|
Sign up to set email alerts
|

A priori assessment of ecotoxicological risks linked to building a hospital

Abstract: Hospital wastewaters contain a large number of chemical pollutants such as disinfectants, detergents, and drug residues. A part of these pollutants is not eliminated by traditional urban waste water treatment plants, leading to a major risk for the aquatic ecosystems receiving these effluents. After having formulated a specific methodology in order to assessment ecotoxicological risk for such a situation, we applied it to the project to build a new hospital shared by several towns in the French Alps. This meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 56 publications
3
13
0
2
Order By: Relevance
“…By supposing that a high input of nutriments could mask a residual toxicity of treated effluents, a 100 % EQ organic extract was also tested but resulted in no measurable growth inhibition (Table 1). A similar result was also shown in Perrodin et al (2013) where exposure of P. subcapitata to a hospital effluent biologically treated did not result in any algal growth inhibition. It can be concluded that either these effluents have actually no effect on algal growth and/or that this assay is not well adapted to evaluate the toxicity of a complex mixture of chemicals, pesticides, and pharmaceuticals likely to be found in the WWTP samples.…”
Section: Standardized Algal and Ostracode Growth Inhibition Tests Rosupporting
confidence: 84%
See 1 more Smart Citation
“…By supposing that a high input of nutriments could mask a residual toxicity of treated effluents, a 100 % EQ organic extract was also tested but resulted in no measurable growth inhibition (Table 1). A similar result was also shown in Perrodin et al (2013) where exposure of P. subcapitata to a hospital effluent biologically treated did not result in any algal growth inhibition. It can be concluded that either these effluents have actually no effect on algal growth and/or that this assay is not well adapted to evaluate the toxicity of a complex mixture of chemicals, pesticides, and pharmaceuticals likely to be found in the WWTP samples.…”
Section: Standardized Algal and Ostracode Growth Inhibition Tests Rosupporting
confidence: 84%
“…Exposure to the treated effluents CAS or CAS+O 3 at both 50 and 95 % had no more effect on ostracode growth (Table 1). Similarly, Perrodin et al (2013) could not show any effects of biologically treated hospital wastewater (50 %) on ostracode growth. Either such treated effluents have no effects on ostracode growth and/or the assay may not be suitable to evaluate the toxicity of wastewater effluents and not sensitive enough to distinguish a difference between the two treatments CAS and CAS+O 3 .…”
Section: Standardized Algal and Ostracode Growth Inhibition Tests Romentioning
confidence: 67%
“…Interesting and useful research has been accomplished dealing with hospital effluent toxicity and assessment of the environmental risk posed by pharmaceutical residues in treated hospital effluent (Boillot et al, 2008;Perrodin et al, 2013;Emmanuel et al, 2004). This is quite a complex problem and is beyond the aim of this manuscript, but some lessons learned from published studies are discussed herein to point out concerns that merit further research.…”
Section: Hospital Effluent Toxicity and Environmental Risk Assessmentmentioning
confidence: 99%
“…Par ailleurs, avec des CE50 se situant entre 1 et 10 %, selon l'organisme considéré, ce rejet général du site se situe dans la gamme des valeurs d'écotoxicité observées pour divers effluents hospitaliers dans différentes études récentes (BOILLOT et al, 2008;EMMANUEL, 2004;EMMANUEL et al, 2005;ORIAS et PERRODIN, 2013;PERRODIN et al, 2013;PERRODIN et al, 2016).…”
Section: Ecotoxicité Des Rejetsunclassified
“…Cette substance est aussi un des composés organochlorés généralement retrouvé dans les effluents hospitaliers (EMMANUEL et al, 2005;ORIAS et al, 2013;PERRODIN et al, 2013;BOILLOT et al, 2008).…”
unclassified